2015
DOI: 10.1063/1.4916943
|View full text |Cite
|
Sign up to set email alerts
|

Super-Joule heating in graphene and silver nanowire network

Abstract: Transistors, sensors, and transparent conductors based on randomly assembled nanowire networks rely on multi-component percolation for unique and distinctive applications in flexible electronics, biochemical sensing, and solar cells. While conduction models for 1-D and 1-D/2-D networks have been developed, typically assuming linear electronic transport and self-heating, the model has not been validated by direct high-resolution characterization of coupled electronic pathways and thermal response. In this lette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 27 publications
3
55
0
1
Order By: Relevance
“…Here, the graphene works as a barrier to moisture to prevent oxidation and corrosion. Experiments show stable resistance even after years of exposure to moisture [20,61].…”
Section: Stability In Atmospheric Conditionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Here, the graphene works as a barrier to moisture to prevent oxidation and corrosion. Experiments show stable resistance even after years of exposure to moisture [20,61].…”
Section: Stability In Atmospheric Conditionsmentioning
confidence: 99%
“…Self-heating in nanonet TCEs have been characterized carefully and in detail. It has been demonstrated that percolation plays an important role in heat conduction in these networks [63], the thermal bottlenecks are reflected in the formation of hotspots and the heating in these hotspots scales superlinearly with current [61], and most importantly, hotspots may eventually seed the fracture of the film [77]. Obviously, self-heating will accelerate oxidation and corrosion of the films.…”
Section: Stability Against Self-heatingmentioning
confidence: 99%
See 3 more Smart Citations